Modelling Volatility and Leverage Effect in Container Freight Market - Memişoğlu, Reha; Başer, Sadık Özlen (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Shipping is highly volatile, cyclical, and capital-intensive industry based on the prevailing price levels, which makes ship-owners or companies to take an account of market volatility to run stable business operations. Thus, knowing volatility structure would put them in healthy decision-making process of portfolio diversifications, hedging and managing freight rate risks and forecasting shipping freights rates. Therefore, modelling the volatility of container freight market provides an effective prediction mechanism, which can enhance the decision-making process among shipping players. The purpose of this study is to examine the properties of volatility in the industry standard Shanghai Containerized Freight Index (SCFI) return values by employing an Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) model. The results of empirical analysis indicate that both volatility persistence and leverage effect are obvious for SCFI, meaning the impact of external shocks in container shipping market are asymmetric. Also, container freight rates require a long time for the effects of the shocks to be disperse on their own. Lastly the results revealed high index sensitivity ratios for the model, which supports the phenomenon of shipping industry being one of the quickest and harshest reflecting sectors to the developments in the global economy.